2019
DOI: 10.1016/j.ijcha.2019.100395
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of left ventricular thrombus formation following acute ST-segment elevation myocardial infarction: A serial cardiac MRI study

Abstract: Aims Left ventricular (LV) thrombus is a complication of acute ST-segment elevation myocardial infarction (STEMI). We determined the incidence and predictors of LV thrombus formation using serial cardiac magnetic resonance (CMR) and two-dimensional echocardiography studies. Methods and results Two hundred and ten patients underwent CMR (median 4 days [IQR 3-7]) and transthoracic echocardiography (median 4 days [IQR 3-7]) early after STEMI presentation with serial follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
(29 reference statements)
3
24
0
2
Order By: Relevance
“…Accordingly, a newly published cardiac magnetic resonance study found LVT in 23.6% of patients with anterior STEMI. 25 In our study, LVT was observed as 13.2% at 6 months follow-up. In agreement with previous studies, 1,24,26 patients with LVT were more likely to have lower LVEF, LVA, and had a higher incidence of the use of GPIIb/IIIa inhibitors.…”
Section: Discussionsupporting
confidence: 53%
“…Accordingly, a newly published cardiac magnetic resonance study found LVT in 23.6% of patients with anterior STEMI. 25 In our study, LVT was observed as 13.2% at 6 months follow-up. In agreement with previous studies, 1,24,26 patients with LVT were more likely to have lower LVEF, LVA, and had a higher incidence of the use of GPIIb/IIIa inhibitors.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, a prospective multicenter study showed that the incidence of LVT among patients with LV dysfunction after anterior myocardial infarction was up to 26% [ 5 ]. Moreover, detection by standard echocardiography may underestimate the incidence, especially in such a high-risk group [ 6 , 7 ]. The existing biomarkers, however, are not sufficient to predict which of the patients with anterior STEMI is prone to develop LVT, and the identification of additional early predictors would, therefore, be of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The management of LVT and associated embolization has been actively debated due to lack of randomized clinical control trials [8,10]. A cross-sectional study evaluating 35 patients with LV apical thrombi determined that the LVT resolved in all patients being treated with aspirin and warfarin.…”
Section: Discussionmentioning
confidence: 99%